Sodium channels and pain - Waxman, Stephen (Henry Stewart Talks, 2009)
Sodium channels: molecular batteries in the nervous system, The molecular revolution teaches us that there are many types of sodium channels, Some types of sodium channels are preferentially expressed in pain-signaling neurons, or are up-regulated in these neurons after injury, Human hereditary pain disorders teach us important lessons about sodium channels and pain